2022
DOI: 10.7759/cureus.30444
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Melanoma of the Genitourinary System: A Systemic Review and Report of Eight Cases

Abstract: Malignant melanoma (MM) of mucosal membranes (excluding anus and head-neck) is a rare but aggressive disease with poor outcomes. The knowledge of this tumor's development, etiology, and management is scarce, mainly due to the low case numbers. We presented eight cases and performed a comprehensive literature review on mucosal MM (between 1970 and 2020). We identified 47 manuscripts on 55 patients with primary mucosal MM (limited to urothelium and vagina) and reviewed demographics, tumor specifications (morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Adjuvant therapy is often required [ 13 ]. Pelvic exenteration may be beneficial for vaginal melanoma and female urethral melanoma with a thickness of more than 3 mm [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant therapy is often required [ 13 ]. Pelvic exenteration may be beneficial for vaginal melanoma and female urethral melanoma with a thickness of more than 3 mm [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, gynecologic tract melanoma has a poor prognosis, with a 5-year survival rate lower than 25%. Because of the low survival rate and the lack of a standard treatment approach related to gynecologic tract melanoma [1][2][3], elucidation of the mechanisms underlying melanoma progression is crucial for achieving advancements in relevant gynecological surgery and treatment. Studies have indicated that extracellular signal-regulated kinase (ERK) and phosphoinositide 3-kinase/protein kinase B (AKT) pathways play major roles in the progression of melanoma [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The most common regions impacted in the genitourinary tract by malignant melanoma are the urethral meatus and distal urethra, although less commonly the bladder and ureter can be affected as well [2][3][4]. Unlike cutaneous melanoma, there is a lower incidence of BRAF mutations in mucosal melanomas; PI3K/Ak strain transforming (Akt)/mammalian target of rapamycin (mTOR) pathway alterations and c-kit mutations are more commonly observed in this group of neoplasms [5]. Poor outcomes for patients are typically due to the invasive nature and late diagnosis of the condition; the estimated three-year survival rate upon diagnosis is under 5% [1].…”
Section: Introductionmentioning
confidence: 99%